Worksheet Development based on RE-STEM for Science Literacy and Character - Arifah, Tutik; Trisnowati, Eli; Singgih, Suwito; Muhlisin, Ahmad; Siswanto, Siswanto; Juliyanto, Eko; Ismawati, Riva; Dewantari, Nuryunita; Rahayu, Rina (Universitas Islam Negeri Raden Intan Lampung, 2022)
There have been several cases that reflect the moral and character decline of Indonesian students. Based on some previous studies that have been carried out, ethnoscience and STEM-based worksheet can improve scientific literacy skills and grow students’ character. The aims of this research are to test the feasibility of RE-STEM-based (Religious, Ethnosains-Science, Technology, Engineering, and Mathematics) science worksheet to improve students' scientific literacy and character, and to find out the students' responses to science worksheet based on RE-STEM as an effort to improve students’ scientific literacy and character. This research applies the development research method with the ADDIE model. The sources of data in this study are the results of expert validations and student response questionnaires, while the research subjects are the experts and students. Data collection techniques and instruments in this study used the expert validation sheets and student response questionnaire sheets. The data analysis technique consists of two things namely the worksheet feasibility test using the V'Aikens value, and the student response test using the Likert scale of student responses which is then converted to a score interpretation table of five criteria. The results showed that the validity of the developed worksheet was categorized as valid with an average V'Aikens value of 0.86, so that the product developed was feasible to use, while the students’ response after using such the developed worksheet is very good with a percentage of 86.17 percent. Thus, the developed RE-STEM worksheet has accomplished the validity requirements and received a good response from students, so that it can be implemented in the learning process.